Wait Times for Sleep Apnea Care in Ontario: A Multidisciplinary Assessment - Brian W Rotenberg; Charles F George; Kevin M Sullivan; Eric Wong (Canadian Respiratory Journal)
BACKGROUND: Obstructive sleep apnea (OSA) is a highly prevalent disorder that is associated with significant patient morbidity and societal burden. In general, wait times for health care in Ontario are believed to be lengthy; however, many diseases lack specific corroborative wait time data.